Cortical hyperexcitability in patients with C9ORF72 mutations: Relationship to phenotype. Issue 2 (25th May 2016) - Schanz, Olivia; Bageac, Devin; Braun, Laura; Traynor, Bryan J.; Lehky, Tanya J.; Floeter, MARY Kay
ABSTRACT: Introduction: Patients with mutations in C9orf72 can have amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), or ALS‐FTD. The goals were to establish whether cortical hyperexcitability occurs in C9orf72 patients with different clinical presentations. Methods : Cortical thresholds and silent periods were measured in thenar muscles in 19 participants with C9orf72 expansions and 21 healthy controls using transcranial magnetic stimulation (TMS). El Escorial and Rascovsky criteria were used to diagnose ALS and FTD. Fourteen participants with C9orf72 expansions were re‐tested 6 months later. Correlations with finger‐tapping speed, timed peg test, the ALS functional rating scale, and Dementia Rating Scale were examined. Results : Most participants with C9orf72 expansions had normal or low cortical thresholds. Among them, ALS patients had the lowest thresholds and significantly shorter silent periods. Thresholds correlated with timed peg‐test scores. TMS did not correlate with the Dementia Rating Scale. Conclusions : TMS measures of cortical excitability may serve as noninvasive biomarkers of ALS disease activity. Muscle Nerve, 2016 Muscle Nerve 54 : 264–269, 2016